2018
DOI: 10.1002/anie.201801380
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Chromium Catalysts with Chain Transfer Agents: A Route to Isotactic Poly(propylene oxide)s with Narrow Dispersities

Abstract: Bimetallic chromium catalysts are investigated for the enantioselective polymerization of propylene oxide. The catalyst is composed of two salen chromium species linked by an alkyl chain, the length of which significantly impacts the rate of polymerization. While the use of a chloride initiator on the catalyst resulted in bimodal molecular weight distributions, switching to a trifluoroacetate initiating group and adding a diol chain transfer agent afforded polymers of controllable molecular weight with low, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
1
35
0
2
Order By: Relevance
“…In these prior ROCOP studies the formation of ether linkages or blocks was not observed but the reactions were conducted with equivalent epoxide:anhydride loadings which would prevent observation of epoxide ROP following the alternating enchainment. Additionally, related bimetallic Cr-salen complexes were effective stereoselective propene oxide ROP catalysts, suggesting that under proper conditions the catalysts might be able to enchain polyether blocks 34,35 . It is also worth commenting that previously, [SalcyCrCl] was used in switchable polymerizations of cyclohexene oxide (CHO)/ anhydrides/decalactone to selectively produce poly(ester- b -ester’) without any evidence of ether blocks or linkages.…”
Section: Resultsmentioning
confidence: 99%
“…In these prior ROCOP studies the formation of ether linkages or blocks was not observed but the reactions were conducted with equivalent epoxide:anhydride loadings which would prevent observation of epoxide ROP following the alternating enchainment. Additionally, related bimetallic Cr-salen complexes were effective stereoselective propene oxide ROP catalysts, suggesting that under proper conditions the catalysts might be able to enchain polyether blocks 34,35 . It is also worth commenting that previously, [SalcyCrCl] was used in switchable polymerizations of cyclohexene oxide (CHO)/ anhydrides/decalactone to selectively produce poly(ester- b -ester’) without any evidence of ether blocks or linkages.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, other catalysts exposed to mixtures of PO/LA yielded either only isotactic PLA or formed 3,6‐dimethyl‐1,4‐dioxan‐2‐one (lactone) . Other side reactions could be PO ring‐opening polymerisation (ROP) to polyethers and/or unselective ring‐opening copolymerisation (ROCOP) to form poly(ether‐ester)s . Overall, these particular monomers bring additional complexities and potential side reactions compared to previous studies, and these problems must be overcome for successful switch catalysis.…”
Section: Methodsmentioning
confidence: 99%
“…To address these shortcomings, numerous catalytic strategies have been reported for epoxide polymerizations. Catalytic methods can result in polymers and also copolymers , with high molecular weight, narrow dispersity, and controlled stereochemistry. However, the catalyst synthesis in these methods can be complex and/or use expensive starting materials, making them less suitable for nonexperts that may want to utilize polyether materials.…”
Section: Introductionmentioning
confidence: 99%